Strategies for Successful Research to Application Projects: A Case Study of the National Sea Grant College Program - Jones, Hollis R.; Briggs, Rebecca A.; Krepp, Alison; Rohring, Elizabeth (Frontiers in Marine Science, 2021)
As coastal landscapes change, management professionals are working hard to transition research results into actions that support scientifically informed decisions impacting coastal communities. This type of research faces many challenges due to competing priorities, but boundary spanning organizations can help mediate these conflicts by forming transdisciplinary collaborations. The National Sea Grant College Program, a National Oceanic and Atmospheric Administration based agency, is a networked organization of 34 university-based state programs that uses a three pronged approach of research, extension, and education to move academic research into the hands of stakeholders and decision makers. The objective of this study is to better understand strategies for successful research to application (R2A) projects that address complex environmental problems occurring in a socio-economic context. Specifically, this work examines R2A projects from the Sea Grant network to better understand the drivers for project development and common deliverables produced through the R2A process. We also identify five common facilitating factors that enabled ‘successful’ R2A across all projects: platforms for partnerships, iterative communication, transparent planning, clear examples of R2A, and graduate student involvement. By providing examples of successful frameworks, we hope to encourage more organizations to engage in the research to application process.